(untitled) (Research, Society and Development, 2023)
Bovine cysticercosis is one of the main parasitic diseases responsible for the condemnation of carcasses in slaughterhouses throughout Brazil. Considered a zoonosis, caused by the larval form of Taenia saginata (Cysticercus bovis) in bovine tissues, it has man as the only definitive host who acquires the infection by eating raw or undercooked meat containing cysticerci, whereas bovine intermediate hosts are infected by ingestion of viable eggs in pasture or water. The diagnosis of this pathology is carried out during the slaughter of the animals exclusively by the sanitary inspection service, carcasses that present exorbitant infestations are immediately condemned, moderate presence of cysticercosis lead to partial condemnation according to the recommendations of the RIISPOA in force and updated in 2017, but they depreciate the carcasses considerably, reducing the prestige and value of the product, causing significant losses to the entire production chain. Therefore, this study aimed to carry out an epidemiological survey of the occurrence of bovine cysticercosis in a slaughterhouse located in the northwest region of the State of Paraná from June 2021 to July 2022, using official data provided by the Agricultural Defense Agency of the State of Paraná (ADAPAR). The data collection was carried out through the monthly epidemiological reports made available by ADAPAR, in the evaluated period, being the observation and notification of its occurrence obtained through the post-mortem inspection carried out by qualified veterinarians, with records in nosographic maps of daily slaughter, informing the number of slaughtered animals, carcasses and organs affected with injuries and number of diseases found. The data in numbers obtained were analyzed from a simple analysis using the Excel software, comparing the number of slaughtered animals with the total number of carcasses that presented injuries and their respective percentages. A total of 11,263 cattle from the 61 municipalities that make up the northwest region of Paraná were slaughtered, a total of 50 carcasses had cysticercosis, corresponding to a prevalence of 0.44% of infection, in data per year only in the second half of 2021, 6,144 were slaughtered cattle, where 2 had cysticercosis (0.03%) already in the first half of 2022, a total of 5,119 cattle were slaughtered, where 48 carcasses had cysticercosis (0.94%). Comparing with previous reports in the same region, the prevalence rate showed a significant decline, reflecting inspection actions, quality control and adequate production management adopted by producers in the region, however, it is noteworthy that even the value found is considerably low, still shows economic damage to cattle farming in this region and it is emphasized that the sanitary measures adopted must be reviewed and strictly followed by the entire production chain.